Implementasi Manajemen Strategik Kepala Sekolah di SMPN 1 Janapria - Sukranudin (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2024)
Implementing internal strategies management involves effort in transforming objective strategies into the action that is organizing school programs. However, something strategic is not implemented with Good Of course just No will be meaningful in environmental organization education. The researcher aims to analyze condition objectives and obstacles faced head school in the implementation management strategy head Janapria 1 Middle School. Study with approach qualitative. Data mining was carried out through interviews, observation, and documentation. The study taking place over six months involves the Head of Schools, the Deputy Head of Curriculum, the Deputy Head of Student Affairs, the Deputy Head of Public Relations, the Deputy Head of Infrastructure, and Teachers. Studies show that condition objective implementation management implemented strategy head school held start planning, organizing, implementing and supervising in the field curriculum, student affairs, infrastructure, public relations, and teachers. The problem is the indiscipline of power educators and education, miscommunication, and misinformation between teachers, and lack of Power support like infrastructure, facilities, and budget schools. The strategy implemented in managing a school is in the field curriculum, implement curriculum latest, in the field student affairs, prioritizing coaching students as well as channeling talents and interests students, in the field means infrastructure, develop fulfillment facilities, facilities, and infrastructure in accordance needs, in the field connection community, outreach, and publication school held through majlis taklim, improve teacher competence and professionalism.